DETERMINATION OF THE EXTRACTION METHOD OF BIOLOGICA L ACTIVE SUBSTANCES OF YANTOQ (ALHAGI MAURORUM) PLANT GROWN IN KASHKADARYA REGION - Sattorova , Komola A.; Kholmurodov , Bakhodir B. (Mental Enlightenment Scientific-Methodological Journal, 2024)
The creation, testing and application of new types of products to the masses is based on benefiting a certain person. The technology of obtaining supplements and extracts containing biologically active substances is based on the bioactive substances in the component of the product. In our review, the extraction method was used to extract the bioactive substances of the yantak plant (alhagi maurorum) with respect to the content of flavonoids. In the process of analysis, 16 different extraction samples were prepared and structural and quantitative analysis of flavonoids was carried out using high-performance liquid chromatography. Optimal parameters were selected according to the analysis process.